The fabrication of a customized occlusal splint based on the merging of dynamic jaw tracking records, cone beam computed tomography, and CAD-CAM digital impression - Katerina Aslanidou; Chung How Kau; Christos Vlachos; Tayem Abou Saleh (Wolters Kluwer Medknow Publications, 2017)
OBJECTIVES: The aim of this case report was to present the procedure of fabricating a customized occlusal splint, through a revolutionary software that combines cone beam computed tomography (CBCT) with jaw motion tracking (JMT) data and superimposes a digital impression. MATERIALS AND METHODS: The case report was conducted on a 46-year-old female patient diagnosed with the temporomandibular disorder. A CBCT scan and an optical impression were obtained. The range of the patient's mandibular movements was captured with a JMT device. The data were combined in the SICAT software (SICAT, Sirona, Bonn, Germany). RESULTS: The software enabled the visualization of patient-specific mandibular movements and provided a real dynamic anatomical evaluation of the condylar position in the glenoid fossa. After the assessment of the range of movements during opening, protrusion, and lateral movements all the data were sent to SICAT and a customized occlusal splint was manufactured. CONCLUSIONS: The SICAT software provides a three-dimensional real-dynamic simulation of mandibular movements relative to the patient-specific anatomy of the jaw; thus, it opens new possibilities and potentials for the management of temporomandibular disorders.